2016
DOI: 10.1128/jcm.02832-15
|View full text |Cite
|
Sign up to set email alerts
|

Direct Identification of Urinary Tract Pathogens from Urine Samples, Combining Urine Screening Methods and Matrix-Assisted Laser Desorption Ionization–Time of Flight Mass Spectrometry

Abstract: Early diagnosis of urinary tract infections (UTIs) is essential to avoid inadequate or unnecessary empirical antibiotic therapy. Microbiological confirmation takes 24 to 48 h. The use of screening methods, such as cytometry and automated microscopic analysis of urine sediment, allows the rapid prediction of negative samples. In addition, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) is a widely established technique in clinical microbiology laboratories used to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 23 publications
3
56
1
1
Order By: Relevance
“…First, our pediatric population had a median age of 7 years, which might make the data difficult to generalize to adult populations. However, our percent culture positivity and distribution of uropathogens were comparable to the same data reported from adult settings (13). Second, the majority of positive urine cultures in this study were monomicrobial infections with E. coli (n ϭ 57; 70.4% of monomicrobial infections).…”
Section: Discussionsupporting
confidence: 65%
“…First, our pediatric population had a median age of 7 years, which might make the data difficult to generalize to adult populations. However, our percent culture positivity and distribution of uropathogens were comparable to the same data reported from adult settings (13). Second, the majority of positive urine cultures in this study were monomicrobial infections with E. coli (n ϭ 57; 70.4% of monomicrobial infections).…”
Section: Discussionsupporting
confidence: 65%
“…As reported previously by others, the analysis of polymicrobial cultures did not provide reliable results (15,20). In our study, nine polymicrobial urine samples provided the correct identification of one microorganism, which is similar to Inigo et al who showed that 75% of the polymicrobial urine samples provided invalid results (15).…”
Section: Urine Culture Identification Maldi-tof Ms Identificationsupporting
confidence: 73%
“…The most appropriate volumes of the urine sample, formic acid, acetonitrile (15 ml, 3 l, and 3 l, respectively) and 3 l of supernatant spotted onto the target plate showed LODs of 1.0 ϫ 10 5 , 4.0 ϫ 10 5 , and 1.52 ϫ 10 5 CFU/ml for E. coli, K. pneumoniae, and E. faecalis, respectively, which were equivalent to those previously reported on the Bruker Biotyper system (17). Inigo et al established 2 ml as the optimum volume, as it was easily manipulated in Eppendorf tubes and centrifuges (15). Zboromyrska et al used 10 ml of urine for MALDI-TOF MS and obtained higher score values of direct identification (16).…”
Section: Urine Culture Identification Maldi-tof Ms Identificationmentioning
confidence: 99%
See 2 more Smart Citations